OPTIMALISASI DIGITAL BANKING: UPAYA MEMINIMALISIR RISIKO TEKNOLOGI INFORMASI - Enny Puji; Enny Puji Lestari; Nyimas Lidya Putri Pertiwi,M.Sy; Siti Zulaikha (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
Technological advances in banking have begun to develop in line with the existence of digital technology to provide customer satisfaction level services so that economic stability increases. In this research, the author focuses on BPRS MAU syariah and BPRS Bandar Lampung, as for the purpose of this research to see the extent of digital banking optimization at BPRS Bandar Lampung and BPRS MAU Syariah, and efforts to minimize the occurrence of information technology risks at BPRS MAU Syariah and BPRS Bandar Lampung seen from the benefits of digitizing customer satisfaction, as well as the impact of trust for customers and banks. Research Results Optimization of BPRS MAU Syariah and BPRS Bandar Lampung, must continue to be improved on understanding and awareness of the importance of bank digitalization, which greatly affects the impact of trust for customers and banks. So that financial stability in BPRS is increased and the quality of service can have an impact on product loyalty as a sense of satisfaction, willingness to pay more and willingness to move to other products. The use of information technology whose operations experience risks is caused by; (i) weak governance of BPRS technology in the use of digital technology, (ii) the uncontrolled complexity of information technology assets in system and human resource needs where these needs of BPRS still have to be increased so that the value of needs attached to financial stability can have an impact on customer satisfaction.